Influence of sleep duration on cortical oxygenation in elderly individuals. Issue 1 (11th December 2016) - Kato, Kazuko; Miyata, Seiko; Ando, Motoo; Matsuoka, Hiroki; Yasuma, Fumihiko; Iwamoto, Kunihiro; Kawano, Naoko; Banno, Masahiro; Ozaki, Norio; Noda, Akiko
Abstract : Aim: Short sleep duration is a risk factor for cardiovascular diseases. Cerebral blood flow and its regulation are affected by pathological conditions commonly observed in the elderly population, such as dementia, atherosclerosis, diabetes mellitus (DM), stroke, and hypertension. The purpose of this study was to examine the influence of sleep duration on cortical oxygenated hemoglobin (OxyHb) using near‐infrared spectroscopy (NIRS). Methods: Seventy‐three individuals (age, 70.1 ± 3.9 years, 51 men and 22 women) participated in this study. Cortical OxyHb levels were measured with NIRS. We evaluated age, body mass index (BMI), smoking status, alcohol intake, sleep duration, hypertension, DM, and hyperlipidemia using a questionnaire. Blood pressure was measured using plethysmography. Results: Peak OxyHb and area under the NIRS curve significantly decreased in participants with sleep duration <7 h compared with those with sleep duration ≥7 h (0.136 ± 0.212 mM·mm vs 0.378 ± 0.342 mM·mm, P  = 0.001; 112.0 ± 243.6 vs 331.7 ± 428.7, P  = 0.012, respectively). Sleep duration was significantly correlated with peak OxyHb level and area under the NIRS curve ( r  = 0.378, P  = 0.001; r  = 0.285, P  = 0.015, respectively). Multiple regression analysis, including age, BMI, sex, smoking status, alcohol intake, sleep duration, hypertension, DM, and hyperlipidemia revealed that sleep duration was the only significant independent factor associated with peak OxyHb and area under the NIRS curve ( β  = 0.343, P  = 0.004; β  = 0.244, P  = 0.049, respectively), and smoking status was independently correlated with time to the peak OxyHb ( β  = −0.319, P  = 0.009). Conclusion: Sleep duration may be an important factor that influences cortical oxygenation in the elderly population.